WHO IS AN ONLINE TRADER FROM THE CONSUMER LAW PERSPECTIVE? FROM SERBIA TO THE EU AND BACK - Radonjić, Aleksa Lj (Pravni zapisi, 2023)
The author seeks to answer the following research question: If a natural person is not a registered entrepreneur but does sell goods or services online regularly and for-profit, does that make that person a trader for the purposes of consumer law? The method applied is legal dogmatic. It is a search for the meaning of one of the key notions in consumer law, the trader. The meaning of this notion in Serbian legal literature has been taken for granted, or it has been controversially interpreted by certain consumer protection organizations, and the relevant case law does not exist, making this analysis even more needed. The author concludes that the definition of a trader from Serbian Consumer Protection Act may be interpreted encompassing a natural person who is not an entrepreneur, who sells goods or services online to consumers, depending on the circumstances of the case. The conclusion is based on the analysis of relevant CJEU case law and the case law of some EU Member States.